Gender Dimensions of Pension Reform in the Former Soviet Union - Castel, Paulette (World Bank, Washington, DC, 2014)
The authors analyze the gender implications of pension reform in Kazakhstan, the Kygyz Republic, Latvia, and Moldova. The new systems deliberately penalize early retirement and reward longer careers, so that with no change in behavior or policy, women's pensions will be lower than men's on average. Still, the implicit financial returns for women remain higher on average than returns for men, because of women's longer life expectancy and because of redistributory minimum pensions. Overall, however, the net change in wealth resulting from the reforms will be larger on average for men than for women, because they will work longer and get a larger pension. Women's longer life expectancy means that women can expect to spend the last years of their lives alone. If their pensions are too low because of their work histories, poverty among elderly women may increase.